THE RELATIONSHIP BETWEEN SCHOOL ADMINISTRATORS’ LEADERSHIP AND TEACHERS’ JOB SATISFACTION IN THE NONGBOONMAK 2 NETWORK OF EDUCATION DEVELOPMENT CENTER THE OFFICE OF NAKHONRATCHASIMA PRIMARY EDUCATION AREA 2 - Chiangklang, Charobon; Chuntaruthai, Somying (Journal of MCU Nakhondhat, 2020)
The purposes of this research were to 1) examine the transformational leadership of the administrators of the schools in Nongboonmak Educational Quality Development Network Center 2 2) investigate the job satisfaction of the teachers of the schools in Nongboonmak Educational Quality Development Network Center 2 and 3) examine the relationship between the transformational leadership of the administrators and the job satisfaction of the teachers of the schools in Nongboonmak Educational Quality Development Network Center 2. The study sample consisted of 76 teachers of the schools in Nongboonmak Educational Quality Development Network Center 2. The instrument used for collecting the data was a 5 – point rating scale questionnaire. The statistics used for analyzing the collected data were percentage, mean, standard deviation and Pearson’s Product Moment Correlation Coefficient. The research findings were as follows: 1) the transformational leadership of the administrators of the schools in Nongboonmak Educational Quality Development Network Center 2 was performed at high level in whole and in part 2) the level of job satisfaction of the teachers of the schools in Nongboonmak Educational Quality Development Network Center 2 was at high level in whole and in part and 3) the relationship between the transformational leadership of the administrators and the job satisfaction of the teachers of the schools in Nongboonmak Educational Quality Development Network Center 2 was positively at high level at the .01 level of significance. After item analysis, it was found that the administrators’ inspiration and intellectual stimulation positively correlated with job satisfaction of the teachers of the schools in Nongboonmak Educational Quality Development Network Center 2 at moderate level. Others aspects of the administrators’ transformational leadership related to the teachers’ job satisfaction at high level.